Development of MATLAB-Based Physics Practical Media to Optimize Online Learning for Students on Sine Wave Material - Astalini, Astalini; Qizi, Karimova Charos Abduhalim; San, Min Thu; Yusifov, Sabuhi; Byamba-Ochir, Narandalai (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to develop MATLAB-based learning media as an interactive online practicum tool to understand the concept of sine waves. Methodology: The research method uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research subjects are physics education students at Jambi University, data collection techniques using questionnaires. MATLAB-based media is designed with interactive simulation features that allow students to manipulate sine wave parameters, such as frequency, amplitude, and phase, in real-time. Main Findings: The test results showed that the majority of students responded positively to the use of this media, with 60% in the